Household food security status and its associated factors among pensioners in Arba Minch town, South Ethiopia - Mamo, Daniel Niguse; Worku, Kassahun Misgana; Adem, Yonas Fissha; Shibabaw, Adamu Ambachew; Habte, Aklilu; Haile, Yosef (Frontiers in Nutrition, 2024)
Introduction: Food insecurity remains a serious public health problem in developing countries over the past two decades, including Ethiopia. Vulnerable populations such as pensioners were affected by this problem because of the emerging socio-demographic changes, a global financial crisis, and climate change that have led to the high prices of food. Hence this study aimed to assess household food security status and associated factors among pensioners in Arba Minch town, South Ethiopia.A community-based cross-sectional study design was employed from September to October 2023. Two hundred forty-four pensioners were chosen using a simple random sampling technique. Data were collected, cleaned, and entered into EPI-Data version 4.6 and exported to Stata SPSS version 2514 for analysis. Variables with p ≤ 0.25 in the bivariate analyses were candidates for multivariable regression analysis. In multivariable logistic regression, variables with a p-value of 0.05 were considered to have a significant association with the dependent variable.Results: A total of 238 retired people were interviewed, with a response rate of 97.5 percent.Among interviewed pensioners, 223(91.4%) households were food insecure. Having greater than one dependent member [AOR=2.4, 95% C.I: 1.30, 6.64], being jobless after retirement [AOR=3, 95% C.I:1.17, 5.61], and being in the lowest tertile of wealth status [AOR=2, 95% C.I:1.36, 4.99] were predictors of food insecurity.The magnitude of household food insecurity was higher compared to the national average, and factors such as the current occupational status of the household head, dependency ratio, and wealth status of the household were significantly associated with household food insecurity. Therefore, policymakers and programmers should provide new strategies focusing on additional income-generating activities and salary increments and consider free services like school fees and health care.